Pitch: a key factor in tonality induction - Anta, Juan Fernando (2015)
Two experiments investigated the role of pitch-related information in tonality induction. In both experiments, participants were asked to: 1) identify (sing) the tonic of either an original sequence of tones or a distorted version in which pitch class distribution was preserved but pitch class ordering, pitch contour, and/or pitch proximity were altered; and 2) rate how confident they were in the tonic they identified. In Experiment 2, the sequences were presented with an isochronous rhythm, in order to eliminate the potential confounding effects of time-related information. The results of both experiments showed that participants’ ability to identify the tonic of the sequences, as well as their confidence in the tonic they identified, decreased when pitch class ordering was distorted, and also when pitch proximity was reduced. This suggests that tonality induction not only involves the identification of abstract pitch class structures, but it also acts as a pattern-matching process.